2013
DOI: 10.1002/clen.201200401
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Atmospheric CO2 Enhances Copper Uptake in Crops and Pasture Species Grown in Copper‐Contaminated Soils in a Micro‐Plot Study

Abstract: The biomass of plants for the purpose of phytoremediation is often small. Carbon dioxide (CO2) can enhance plant biomass and so, it is reasonable to draw such an assumption that CO2 can be used to help plants to phytoremediate heavy metal contaminated soils through enhancing the biomass of remediating plants. To identify this assumption, a micro‐plot study in six separate growth chambers was conducted to investigate the effect of high CO2 levels (approximately 1000 ± 50 µL L−1) on Cu accumulation and the remed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Plants growing under eCO 2 had a higher concentration of Cu, a response that has been observed previously (Tian et al, 2013), higher B and S content and the eCO 2 soil a higher B content. The values for these elements were in the "adequate" range recommended for pastures (Fleming 2003).…”
Section: Biogeosciencessupporting
confidence: 81%
“…Plants growing under eCO 2 had a higher concentration of Cu, a response that has been observed previously (Tian et al, 2013), higher B and S content and the eCO 2 soil a higher B content. The values for these elements were in the "adequate" range recommended for pastures (Fleming 2003).…”
Section: Biogeosciencessupporting
confidence: 81%
“…When it comes to the quality of oil crops, the limited research available indicates that elevated [CO 2 ] may have a positive effect, but certainly there are also negative impacts on oil quality by changing the composition of FAs on a dry weight basis. Illustrated by the handful of studies available on a very limited number of cultivars in sunflower ( Pal et al , 2014 ), castor bean ( Vanaja et al , 2008 ) and rapeseed ( Högy et al , 2010 ; Tian et al , 2014 ), the crop quality response to elevated [CO 2 ] is not unequivocal. A growth chamber study of the rapeseed cultivar ‘Mozart’ – likely the same cultivar also analysed in the present study – demonstrated decreased seed oil% as well as seed yield, while vegetative biomass increased ( Franzaring et al , 2011 ; [CO 2 ] 550ppm).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that in the future further increases in global CO 2 levels and contamination with heavy metals are likely, it is important to do more studies on the physiological response of crops. Although recently a few studies have assessed this problem, they were based on the accumulation of metals in plants without consideration of the physiological response in plants [9,16,17,23,26,34,41,42,45].…”
mentioning
confidence: 99%